Biogas Desulfurization Using Iron Gram Waste Machining Practicum Process at The Department of Mechanical Engineering, Politeknik Negeri Semarang - Apriandi, Nanang; Widyaningsih, Wiwik Purwati; Margana, Margana; Surindra, Mochamad Denny; Supriyo, Supriyo; Luthfiana, Nadia Tasya Ayu (Politeknik Negeri Semarang, 2022)
The important matter about biogas as an alternative energy source was the presence of hydrogen sulfide (H2S) which is very corrosive. The biogas desulfurization process was absolutely necessary to reduce the risk of damage to the equipment. For small-scale applications, the selection of the type of adsorbent became important to reduce additional costs. One alternative material that can be used was iron gram waste. The aim of this study was to investigate the use of iron gram waste resulting from the machining practicum process at the Department of Mechanical Engineering, Politeknik Negeri Semarang as an alternative material for making adsorbents. Iron gram waste was processed into Iron (III) Oxide (Fe2O3) and Iron (III) Hydroxide (Fe(OH)3), formed into billets with an average billet mass of 250 gr. The performance test of the adsorbent in the biogas desulfurization process was carried out under conditions of variation in the flow rate of biogas feed 1, 2, and 3 liters per minute, and the volume of biogas purified in one process was 50 liters. As a result, the most optimum performance was obtained in the test with a feed biogas flow rate of 1 liter/minute, with a percentage reduction in H2S levels contained in the biogas by an average of 82,56%.